IL-22: An Evolutionary Missing-Link Authenticating the Role of the Immune System in Tissue Regeneration - Kumar, Pawan (Ivyspring International Publisher, 2012)
Tissue regeneration is a critical component of organ maintenance. The ability of lymphocytes to kill pathogen-infected cells has been well-studied. However, the necessity for lymphocytes to participate in reconstruction of destroyed tissues has not been explored until recently. Interleukin (IL)-22, a newly defined cytokine exclusively produced by subsets of lymphocytes, provides the strongest proof yet for the tissue regenerative potentials of the immune system. IL-22 plays an obligatory role in epithelial homeostasis in the gut, liver and lung. The receptor for IL-22 (IL-22R1 and IL-10R2) is predominantly expressed by epithelial cells. While the pro-inflammatory effect is questioned, the pro-constructive potential of IL-22 is well established. It is evident from the response to IL-22, that epithelial cells not only produce anti-microbial peptides but also actively proliferate. Aryl hydrocarbon receptor (AhR) and retinoic acid-related orphan receptor (RORγt) transcription factor are required for IL-22 generation from Lymphoid Tissue inducer cells LTi, Th22 and NK-like cells. However, IL-22 production from conventional NK cells is independent of AhR and RORγt. In this review, we present a case for a paradigm shift in how we define the function of the immune system. This would include tissue regeneration as a legitimate immune function.